Cultural, religious and socio-ethical misconceptions among muslim women towards breast cancer screening: a systematic review - Moey, Soo Foon; Sowtali, Siti Noorkhairina; Mohamad Ismail, Mohamad Firdaus; Hashi, Abdurezak Abdulahi; Mohd Azharuddin, Nur Syamimi; Che Mohamed, Norfariha (Asian Pacific Organization for Cancer Prevention, 2022)
Introduction: Breast cancer is the most diagnosed cancer worldwide. With an estimated 685,000 deaths, female breast cancer was the fifth leading cause of cancer mortality worldwide, accounting for 6.9% of all cancer deaths. Previous studies have shown that late detection and delayed diagnosis are associated with advanced-stage breast cancer and poor survival. Factors contributing to non-adherence to breast cancer screening among women were elicited from previous studies. However, few studies have focused on the Muslim community, particularly Muslim women. As such, this systematic review aims to fill this gap by collecting information from studies conducted globally over the past ten years that examined cultural, religious and socio-ethical misconceptions about breast cancer screening among Muslim women. Methods: Following the PRISMA guidelines, literature searches were conducted systematically through various databases including PubMed, Science Direct, Scopus, Cochrane Library and Oxford Academic Journals. Article identification, screening steps and eligibility measures were meticulously performed throughout the review. Results: A total of 22 papers were appraised and included in this review. Five main themes were generated which were socio-ethical misconceptions, cultural and religious beliefs, cultural and religious barriers, stigmatization and fear of breast cancer impact. Eight sub-themes and 14 sub sub-themes were further elicited from the main themes. Conclusion: Muslim women have socio-ethical, cultural and religious misconceptions on what constitutes health and practices as well as on the nature and etiology of BC. Cultural barriers and religious values of Muslim women were indicated to influence their health behaviors such as upholding their modesty when choosing health interventions. BC stigma and fear were also found to be key sources of psychological distress that discouraged Muslim women from undergoing BC screening. The study suggests the implementation of holistic effort in educating Muslim women to increase BC screening rate.